Coordination between real estate and income tax and its impact on the tax outcome: Applied research in the General Authority for Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aimed to demonstrate the possibility of benefiting from the coordination between real estate and income tax as the independent variable on the tax outcome as the dependent variable as the dependent variable. Which were practiced within rented buildings, as information was obtained from real estate owners, and the annual controls for the year 2021 were relied upon in the process of calculating the tax amounts expected to be obtained. used in the tax inventory process lacks seriousness and continuous updating